Inventory costing: a multiplicative-based average for crude oil and petroleum products - Ozyapici, Ali; Ozyapici, Hasan (Taylor & Francis Inc, 2024)
Crude oil prices have been fluctuating nonlinearly in recent times due to various factors, such as market expectations, supply disruptions, and geopolitical conflicts like the Russia-Ukraine and Israel-Palestine crises. However, conventional methods like weighted averages and moving averages are inadequate for accurately capturing these nonlinear changes especially in crude oil prices. This study, therefore, aims to combine multiplicative calculus with weighted and moving average methods to enable accurate calculation of crude oil inventory costing, particularly during times of financial crisis. A comparative study is conducted to highlight the differences between conventional and multiplicative-based average methods. The findings show that the multiplicative-based average yield more accurate results for cost of goods (crude oil or petroleum products) sold, cost of goods inventoried, and gross margins, especially when the change is nonlinear. This paper, which is the first study to combine weighted and moving averages with a new calculus, is unique in the sense that it contributes to the literature by providing an accurate costing framework to respond to the global financial crises associated with the unprecedented increase in the prices of metals, crude oil, and petroleum products.
Keywords: Inventory accounting; moving average; multiplicative-based moving average; multiplicative-based weighted average; multiplicative calculus; M40; M41; C02; C60